Relationship Between Knowledge and Treatment Compliance in Type 2 Diabetes Mellitus Patients - Nawang Wulan Nago Pitasari; Farhan Imba; Innal Saitis; Ferdinta Setyawan; Risna Risna; Fenska Narly Makualaina (Indonesian Journal of Global Health Research, 2026)
Type 2 diabetes mellitus is a chronic disease with increasing prevalence and requires long-term adherence to therapy to prevent complications. Treatment adherence in diabetes patients remains a challenge, influenced in part by the patient's level of knowledge about the disease and its treatment. This study aims to analyze the relationship between the level of knowledge and adherence to medication therapy in type 2 diabetes mellitus patients at Harapan Community Health Center, Jayapura Regency. This study used a non-experimental quantitative design with a cross-sectional approach. The study sample consisted of 50 type 2 diabetes mellitus patients selected using a total sampling technique. The research instruments used were the Diabetes Knowledge Questionnaire-24 (DKQ-24) to measure the level of knowledge and the Morisky Medication Adherence Scale-8 (MMAS-8) to measure medication adherence. Data analysis was performed univariately and bivariately using the chi-square test with a significance level of 0.05 . The results showed that most respondents had a moderate level of knowledge (54%) and a moderate level of medication adherence (48%). Bivariate analysis showed a significant relationship between the level of knowledge and adherence to medication therapy in type 2 diabetes mellitus patients (p = 0.000). Respondents with a high level of knowledge tended to have better medication adherence.